AB0474 CAROTID CONTRAST ENHANCED ULTRASOUND IN CASES OF TAKAYASU ARTERITIS COMPLICATED WITH BEHCET'S DISEASE. (2nd June 2020) - Fan, W.; Zhu, J.; Yu, P.; Yu, L.; Wang, X.; Wei, X.; Che, D.
Abstract : Background: Carotid contrast enhanced ultrasound (CEUS) is used for diagnosis and activity determination of patients with Takayasu's arteritis (TA). However, very little is known about the carotid CEUS features of TA complicated with Behcet's disease (BD). Objectives: This study reports the carotid CEUS features in cases of TA complicated with BD (TBD). Methods: A total of 10 carotid CEUS examinations were performed on 4 patients of TBD. 10 TA patients complicated with no rheumatoid disease were included as control group. For each carotid artery lesion, the carotid CEUS features was graded as follows: Grade 0, artery wall shows no microbubbles, Grade 1, artery wall shows limited or moderate microbubbles, Grade 2, artery wall shows severe microbubbles. Results: 2/10 patients in TBD group has oral ulcer during the CEUS examination, while all the other patients included in our study showed no clinical symptoms related to active TA or BD. The carotid wall thickness was greater of CEUS grade 2 than grade 1 in both group(TBD: 2.62±0.74mm vs 1.66±0.22mm, p =0.001; TA:1.84±0.31mm vs 1.53±0.5mm, p =0.136). The carotid wall thickness was significantly greater in TBD group than TA group, but there was no significant differences between the two groups in clinical data and CEUS grade (table 1 ). Conclusion: This study first shows carotid CEUS features in cases of TA complicated with BD, which may help with the comprehensive treatments of the disease. Disclosure of Interests: None declared